Risk Stratification Guided by the Index of Microcirculatory Resistance and Left Ventricular End-Diastolic Pressure in Acute Myocardial Infarction. (February 2021) - Maznyczka, Annette M.; McCartney, Peter J.; Oldroyd, Keith G.; Lindsay, Mitchell; McEntegart, Margaret; Eteiba, Hany; Rocchiccioli, J. Paul; Good, Richard; Shaukat, Aadil; Robertson, Keith; Malkin, Christopher J.; Greenwood, John P.; et al.
Abstract : Background: The index of microcirculatory resistance (IMR) of the infarct-related artery and left ventricular end-diastolic pressure (LVEDP) are acute, prognostic biomarkers in patients undergoing primary percutaneous coronary intervention. The clinical significance of IMR and LVEDP in combination is unknown. Methods: IMR and LVEDP were prospectively measured in a prespecified substudy of the T-TIME clinical trial (Trial of Low Dose Adjunctive Alteplase During Primary PCI). IMR was measured using a pressure- and temperature-sensing guidewire following percutaneous coronary intervention. Prognostically established thresholds for IMR (>32) and LVEDP (>18 mm Hg) were predefined. Contrast-enhanced cardiovascular magnetic resonance imaging (1.5 Tesla) was acquired 2 to 7 days and 3 months postmyocardial infarction. The primary end point was major adverse cardiac events, defined as cardiac death/nonfatal myocardial infarction/heart failure hospitalization at 1 year. Results: IMR and LVEDP were both measured in 131 patients (mean age 59±10.7 years, 103 [78.6%] male, 48 [36.6%] with anterior myocardial infarction). The median IMR was 29 (interquartile range, 17–55), the median LVEDP was 17 mm Hg (interquartile range, 12–21), and the correlation between them was not statistically significant ( r =0.15; P =0.087). Fifty-three patients (40%) had low IMR (⩽32) and low LVEDP (⩽18), 18 (14%) had low IMR and high LVEDP, 31 (24%) had high IMR and low LVEDP, while 29 (22%) had high IMR and high LVEDP. Infarct size (% LV mass), LV ejection fraction, final myocardial perfusion grade ⩽1, TIMI (Thrombolysis In Myocardial Infarction) flow grade ⩽2, and coronary flow reserve were associated with LVEDP/IMR group, as was hospitalization for heart failure (n=18 events; P =0.045) and major adverse cardiac events (n=21 events; P =0.051). LVEDP>18 and IMR>32 combined was associated with major adverse cardiac events, independent of age, estimated glomerular filtration rate, and infarct-related artery (odds ratio, 5.80 [95% CI, 1.60–21.22] P =0.008). The net reclassification improvement for detecting major adverse cardiac events was 50.6% (95% CI, 2.7–98.2; P =0.033) when LVEDP>18 was added to IMR>32. Conclusions: IMR and LVEDP in combination have incremental value for risk stratification following primary percutaneous coronary intervention. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02257294. Abstract : Supplemental Digital Content is available in the text.